2015
DOI: 10.1007/s00365-015-9307-1
|View full text |Cite
|
Sign up to set email alerts
|

Location of Poles for the Hastings–McLeod Solution to the Second Painlevé Equation

Abstract: We show that the well-known Hastings-McLeod solution to the second Painlevé equation is pole-free in the region arg x ∈ [− π 3 , π 3 ] ∪ [ 2π 3 , 4π 3 ], which proves an important special case of a general conjecture concerning pole distributions of Painlevé transcedents proposed by Novokshenov. Our strategy is to construct explicit quasi-solutions approximating the Hastings-McLeod solution in different regions of the complex plane and estimate the errors rigorously. The main idea is very similar to the one us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
(61 reference statements)
0
14
0
Order By: Relevance
“…For example, the well-known Hastings-McLeod solution of P II (2) with α = 0 [27], which arises in numerous applications, is a tronquée solution with no poles on the real axis, cf. [28,29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the well-known Hastings-McLeod solution of P II (2) with α = 0 [27], which arises in numerous applications, is a tronquée solution with no poles on the real axis, cf. [28,29].…”
Section: Resultsmentioning
confidence: 99%
“…For example, the well-known Hastings-McLeod solution of P II (1.2) with α = 0 [27], which arises in numerous applications, is a tronquée solution with no poles on the real axis, cf. [28,29,30]. The special solutions q n (z; 0) and p n (z; 0) of P II and P 34 arise in recent study by Clarkson, Loureiro, and Van Assche [24] of the discrete system…”
Section: Discussionmentioning
confidence: 99%
“…where s := (2m 2 ) 1/3 ln(r/r × ). This equation does admit a particular solution-namely the Hastings-McLeod solution b HM (see[9], up to a change of sign x → −x)-which asymptotically satisfies(46) b HM (s) ∼ thus displaying the correct behavior for r → 0. Asymptotic matching with the bulk solution (39) takes care of itself as r → r + × ; there the Hastings-McLeod solution becomes (47) B HM (r) ∼ 2 ln 1…”
mentioning
confidence: 99%
“…However, recently, it was shown that all tritronquée solutions of the Painlevé‐I equation are actually analytic down to the origin in the asymptotically pole‐free sector, proving a conjecture of Dubrovin. See for related results on certain solutions of the Painlevé‐II equation . It is not known whether the tritronquée solutions trueẆ±false(ξ;mfalse) of the Painlevé‐II equation are exactly pole‐free in the sector 23π< Arg false(ξfalse)<23π.…”
Section: Numerical Observations and Formal Scaling Theorymentioning
confidence: 99%